Climate adaptation strategies in Fiji: The role of social norms and cultural values. (July 2018) - Neef, Andreas; Benge, Lucy; Boruff, Bryan; Pauli, Natasha; Weber, Eberhard; Varea, Renata
Highlights: We explore adaptation to climate-related disasters at the community and household level in Fiji, demonstrating its highly situated nature. We demonstrate how the uptake of adaptation strategies is highly contingent upon social structure, hierarchy, and place-based politics. We show how socio-cultural values play a part in determining which risks communities and households are willing to accept and live with. By considering culture and identity as key aspects of secure livelihoods we can understand how these factors influence adaptation choices. Abstract: The Fiji Islands in the South Pacific are highly exposed to climate-induced hazards and have experienced several flood and cyclone events in recent years. Drawing on a series of field studies in the lower Ba River Catchment on Fiji's main island Viti Levu, the objective of this paper is to determine how climate adaptation strategies – employed by indigenous Fijian communities and households – are influenced by socio-cultural values and access to resources, information and power. Our multi-method approach has been conceptually informed by Agrawal and Perrin's (2008) climate adaptation framework and included semi-structured interviews at the household level, and participatory hazard mapping with diverse focus groups at the community level. Our study finds that due to diverse value-based assessments of livelihood opportunities and climate-related risks, communal and household adaptive strategies can differ widely, even in a very localized cultural context. We also show how decisions to relocate from 'risky environments' are influenced by a combination of local power relations, attachment to cultural and social space, and the provision of external assistance. Our findings comment on the need for disaster risk reduction strategies to recognize how different groups and households respond to climate-related events in distinct socially determined ways.